Regeneration of rabbit calvarial defects using cells-implanted nano-hydroxyapatite coated silk scaffolds - Park, Jin-Young (Biomater Res, 2015)
BACKGROUND: The aim of this study was to characterize the efficacy of nano-hydroxyapatite-coated silk fibroin constructs as a scaffold for bone tissue engineering and to determine the osteogenic effect of human dental pulp and periodontal ligament derived cells at an early stage of healing in rabbits. 3D silk fibroin constructs were developed and coated using nano-hydroxyapatite crystals. Dental pulp and periodontal ligament cells from extracted human third molars were cultured and seeded onto the silk scaffolds prior to in vivo implantation into 8 male New Zealand White rabbits. Four circular windows 8 mm in diameter were created in the calvarium of each animal. The defects were randomly allocated to the groups; (1) silk scaffold with dental pulp cells (DPSS), (2) silk scaffold with PDL cells (PDLSS), (3) normal saline-soaked silk scaffold (SS), and (4) empty control. The animals were sacrificed 2 (n = 4) or 4 weeks (n = 4) postoperatively. The characteristics of the silk scaffolds before and after cell seeding were analyzed using SEM. Samples were collected for histologic and histomorphometic analysis. ANOVA was used for statistical analysis. RESULT: Histologic view of the experimental sites showed well-maintained structure of the silk scaffolds mostly unresorbed at 4 weeks. The SEM observations after cell-seeding revealed attachment of the cells onto silk fibroin with production of extracellular matrix. New bone formation was observed in the 4 week groups occurring from the periphery of the defects and the silk fibers were closely integrated with the new bone. There was no significant difference in the amount of bone formation between the SS group and the DPSS and PDLSS groups. CONCLUSION: Within the limitations of this study, silk scaffold is a biocompatible material with potential expediency as an osteoconductive scaffold in bone tissue engineering. However, there was no evidence to suggest that the addition of hDPCs and hPDLCs to the current rabbit calvarial defect model can produce an early effect in augmenting osteogenesis.